Cross-Border Tourist Routes: The Potential of Russia’s North- West - Stepanova S. V. (Baltic Region, 2017)
Developing cross-border tourist routes is an effective way of developing cooperation between border regions of Russia and the neighbouring countries. The author presents an approach that interprets cross-border tourist routes as an instrument for the conservation, reproduction, and promotion of natural, cultural, and historical potential and as a means to boost business activities in border regions. This article summarises international practices and presents the theoretical and practical aspects of designing and developing transboundary tourist routes in the border regions of Russia’s North-West. The author describes successful tourist routes within the European Neighbourhood and Partnership Instrument (ENPI) crossborder cooperation programmes. Particular attention is paid to the routes in the Republic of Karelia — the Blue Road, the White Road, and the Mining Road. The article stresses the importance of developing transboundary tourist routes in the border regions of Russia’s North-West. Designing and developing transboundary tourist routes is a step towards a transboundary tourist space. The author outlines avenues towards the development of transboundary tourist routes and transboundary tourism in the border regions of Russia’s North-West.